Clinical Features and Prognostic Significance of NOTCH1 Mutations in Diffuse Large B-Cell Lymphoma - Li, Zhongqi; Yu, Fang; Ye, Wenle; Mao, Liping; Huang, Jiansong; Shao, Yang; Yan, Junrong; Yu, Wenjuan; Jin, Jie; Wang, Jinghan (Frontiers in Oncology, 2021)
Diffuse large B-cell lymphoma (DLBCL) is a heterogeneous group of large lymphoid B cell malignancy with distinct clinical and genetic features. Recently, NOTCH1 mutations were identified in DLBCL cases by Next-generation sequencing (NGS), but the clinical features and prognostic impact were not systematically studied. Here, NOTCH1 genes in 161 DLBCL samples were sequenced by NGS. The prognostic value of NOTCH1 mutations was assessed in the context of clinical and laboratory factors, such as international prognostic index (IPI), cell-of-origin classification, double expression of BCL2 and c-MYC. The combined data from three Western cohorts were used to validate these results. As a result, NOTCH1 mutations were found in 17(10.6%) patients, and three patients had a hotspot mutation of c.7541_7542delCT. The presence of NOTCH1 mutations was significantly associated with poor complete response and progression free survival(PFS), which was independent of established clinical and laboratory parameters. In addition, 30 (1.92%) of 1562 patients treated with R-CHOP regimen in those combined Western cohorts had NOTCH1 mutations. Meta-analysis of the Western cohorts confirmed that NOTCH1 mutations were also associated with poor PFS and OS. In conclusion, DLBCL patients with the NOTCH1 mutations have worse PFS and OS, and the NOTCH1 mutations can be used as an independent predictor for patients with DLBCL.